Expressed Emotion, Family Functioning, and Treatment Outcome for Adolescents with Anorexia Nervosa. (21st July 2015) - Rienecke, Renee D.; Accurso, Erin C.; Lock, James; Le Grange, Daniel
Abstract: The current study examined the relation between parental expressed emotion (EE) and treatment outcome among adolescents participating in a treatment study for adolescent anorexia nervosa, as well as its impact on family functioning. One hundred and twenty‐one families were assigned to family‐based treatment or adolescent‐focused therapy. Paternal criticism predicted lesser improvement in eating disorder psychopathology at end of treatment. There was also a significant interaction between maternal hostility and treatment, indicating that adolescents whose mothers displayed hostility had greater increases in percent of expected body weight in adolescent‐focused therapy than family‐based treatment. In addition, maternal hostility predicted less improvement in general family functioning and family communication at the end of treatment. Findings suggest that maternal and paternal EE may differentially impact treatment outcome and should be directly attended to in clinical settings. Future research is needed to further explore ways in which parental EE can be effectively modified in treatment. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.